Observation of the suppressed ADS modes B →[πKππ]DKand B →[πKππ]Dπ - Bediaga, I; De Miranda, J; Rodrigues, F; Massafferri, A; Nasteva, I; dos Reis, A; Wilkinson, G; Amato, S; Akiba, K; De Paula, L; Francisco, O; Gandelman, M; et al. (2013)
An analysis of B → DK and B → Dπ decays is presented where the D meson is reconstructed in the four-body nal state Kπππ. Using LHCb data corresponding to an integrated luminosity of 1.0fb1, rst observations are made of the suppressed ADS modes B →[πKππ]D K and B → [πKππ]Dπ with a signicance of 5.1σ and greater than 10σ, respectively. Measurements of CP asymmetries and CP-conserving ratios of partial widths from this family of decays are also performed. The magnitude of the ratio between the suppressed and favoured B → DK amplitudes is determined to be r = 0.097 ±0.011. © 2013 CERN. Published by Elsevier B.V.